2018
DOI: 10.1016/bs.acr.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sphingosine Kinases for the Treatment of Cancer

Abstract: Sphingosine kinases (SK1 and SK2) are key, druggable targets within the sphingolipid metabolism pathway that promote tumor growth and pathologic inflammation. A variety of isozyme-selective and dual inhibitors of SK1 and SK2 have been described in the literature, and at least one compound has reached clinical testing in cancer patients. In this chapter, we will review the rationale for targeting SKs and summarize the preclinical and emerging clinical data for ABC294640 as the first-in-class selective inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 154 publications
(218 reference statements)
0
47
0
Order By: Relevance
“…A study of hispidulin, a polyphenolic flavonoid, found that the treatment shifted the sphingolipid rheostat to ceramide by inhibiting SK1 [ 187 ]. ABC294640 is the first-in-class inhibitor of SK2 and has been clinically tested in a variety of cancers ( Table 2 ) [ 188 ]. ABC294640 has proven effective in both in vitro and in vivo models of TNBC [ 189 ].…”
Section: Altering Sphingolipid Metabolism For Therapeutic Intervenmentioning
confidence: 99%
“…A study of hispidulin, a polyphenolic flavonoid, found that the treatment shifted the sphingolipid rheostat to ceramide by inhibiting SK1 [ 187 ]. ABC294640 is the first-in-class inhibitor of SK2 and has been clinically tested in a variety of cancers ( Table 2 ) [ 188 ]. ABC294640 has proven effective in both in vitro and in vivo models of TNBC [ 189 ].…”
Section: Altering Sphingolipid Metabolism For Therapeutic Intervenmentioning
confidence: 99%
“…These findings suggest that SphK1 inhibitors could be used to treat HNSCC Inhibitors for both SphK1 and SphK2 have been developed. They include N,N-dimethylsphingosine (DMS), SK1-I, SK-I-II, safingol, PF543, FTY720, and ABC294640 [132][133][134][135][136].…”
Section: Sphk Inhibitormentioning
confidence: 99%
“…While our work here focused on translation, a better understanding of the mechanisms of toxicity of SPHK inhibitors should help to optimize their use as anticancer agents by designing better drug combinations. For instance, induction of ER stress by lipotoxicity potentiates the anticancer effects of agents that activate the UPR such as proteasomal inhibitors (38,46). On the other hand, we here show, for the first time, that the toxicity of ISR activators such as Tunicamycin or SKI-II is alleviated by a concomitant treatment with PERKi or ISRIB, although whether this is related to translation remains unknown.…”
Section: Discussionmentioning
confidence: 54%